(untitled) (Proceeding of International Conference on Islamic Economics, Islamic Banking, Zakah and Waqf, 2023)
Objectives: Company value is an investor’s prediction of how big the chance of success of a company is. The value of the company can be seen from the high and low stock prices. This study aims to determine the effect of capital structure, leverage, and profitability on firm value in LQ45 companies for the 2020-2022 period. Methodology: This study uses a quantitative approach using secondary data. The analysis technique used in this study is multiple linear regression. The data test used is the normality test, heteroscedasticity autocorrelation, and hypothesis testing. Finding: The results of the study show that partially capital structure has an effect on firm value with a significance value of 0.000<0.05, leverage has no effect on firm value with a significance value of 0.347>0.05 and profitability has an effect on firm value with a significance value of 0.000<0.05. While simultaneously the capital structure, leverage, and profitability affect firm value with a significant value of 0.000 <0.05.